Is there any link between vitamin D and coronary no-reflow phenomenon? Vitamin D and Coronary No-reflow Phenomenon - Cerit, Levent; Kemal, Hatice; Cerit, Zeynep; Salem, Jane; Dokkmak, Anas; Etikan, Ilker; Duygu, Hamza (Progress in Nutrition, 2019)
Coronary no-reflow phenomenon (CNP) is associated with an increased risk of major cardiovascular adverse events. Vitamin D is closely associated with hypertension, stroke, myocardial infarction, cardiovascular adverse events, and endothelial dysfunction. Considering endothelial dysfunction is one of the main responsible factors of CNP. We aim to evaluate the association between vitamin D and CNP. The study group consisted of 109 patients. Taking into consideration the inclusion criteria, 60 patients with CNP and 49 patients without CNP were included in the study. CNP defined as TIMI grade 3 h, initial TIMI flow